2022
DOI: 10.1055/s-0042-1758859
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Overview of Anorexia Nervosa and Overcoming Treatment Resistance

Abstract: Anorexia nervosa (AN) is a type of eating disorder that has been increasing in incidence and has been encountered more commonly by physicians in their daily practice. Both environmental and genetic risk factors paired along with a more susceptible neurobiology are at play in the emerging resistance to treatment in AN. Preoccupations with intense fear of weight gain, dietary restrictions, excessive exercise, and how the individual is perceived by society mixed with underlying psychopathology all further add to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…AN presents clinicians with significant challenges due to its chronicity, high relapse risk, and considerable morbidity and mortality rates [5][6][7][8]. The ego-syntonic nature of the disorder, characterized by denial and lack of treatment motivation, distinguishes AN from other mental disorders [3,4]. Despite limited scientific evidence on SE-AN treatments, the future holds encouraging prospects for developing more effective therapeutic approaches [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AN presents clinicians with significant challenges due to its chronicity, high relapse risk, and considerable morbidity and mortality rates [5][6][7][8]. The ego-syntonic nature of the disorder, characterized by denial and lack of treatment motivation, distinguishes AN from other mental disorders [3,4]. Despite limited scientific evidence on SE-AN treatments, the future holds encouraging prospects for developing more effective therapeutic approaches [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…About 50–80% of people diagnosed with Anorexia Nervosa (AN) have been estimated to achieve full or partial recovery [ 1 , 2 ] . However, for nearly 20% of patients, the eating disorder (ED) is prolonged and becomes long-lasting [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that children with obesity are more likely to be victims of bullying and have less self-esteem [ 41 - 43 ], which explains these motivators in addition to the adolescent period that increases image obsession [ 44 ]. However, this body image obsession was found to lead to extreme weight loss measures that are unhealthy and sometimes dangerous and can also cause eating disorders [ 45 , 46 ]. Our study found that effective weight loss strategies included consistent physical exercise, and walking was favored.…”
Section: Reviewmentioning
confidence: 99%
“…Anorexia nervosa (AN) is one of the most recognizable, life-threatening eating disorders, commonly beginning during adolescence and early adulthood [ 1 , 2 ]. The median onset age for is approximately 12 [ 3 ], with a remarkable increase in incidence among girls aged 10-14 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%